SALAMAT TURMÍS TÁRIZIN QÁLIPLESTIRIWDE SALAMATLÍQ PSIXOLOGIYASÍNÍŃ ORNÍ - Klicheva, Zulfiya Polatovna (ILIM hám JÁMIYET, 2026)
This article provides information on the role and importance of health psychology in shaping a healthy lifestyle, human psychological well-being, issues of maintaining and strengthening health, as well as the influence of psychological factors on a healthy lifestyle.